Design and evaluation of a programme to assist children cope with divorce - Leibrandt, Cicily (My University, 2014)
The primary purpose of the study was the design and assessment of an intervention programme that seeks to help children cope with the crisis of divorce. The intervention was named the Kids in Divorce (KID) programme and is a short-term, developmentally appropriate intervention, consisting o f 10 sessions, aimed primarily at helping the pre-adolescent child. The aim of the study was to evaluate whether children receiving the intervention showed significant improvements in their emotional and attitudinal coping responses to divorce, as meausuredby the Family1 Story Test (FST) and the Kids in Divorce (KID) questionnaire (a self-designed measure). A pilot study was done on the KID questionnaire in order to, make the necessary changes, before using the questionnaire'for the study. 3 A total of 42 pupils, from schools in th | Eldoradopark 'coloured' community participated in the study. A pre and post test experimental-iBontrol research design was used in the study, The experimental and control groups consisted of 21 children \ each. \ . J r . Results of the study reflected significant improvements measures for the experimental group, which provides strong'cm pirical^nd^^.for'S'ie usefulness of a short-,erm, children cope with parental divorce.
Keywords: Children of divorced parents--South Africa--Counseling of; Children of divorced parents--Education--South Africa; Academic achievement--South Africa